Promoting competent credit score among B40 female entrepreneurs: a case study of Dapur Mawar - Mohd Noor, Nurul Hidayana; Omar, Noralina; Md Zaini, Syeliya; Mohd Beta, Raja Mayang Delima (Universiti Teknologi MARA, Kedah, 2024)
Financial management plays a significant role for every individual, as well as for an entrepreneur. Financial management will affect the credit score, which is one of the determinants of loan approval by financial institutions. This will hurt businesses since entrepreneurs who want to expand their businesses need additional capital injection. Entrepreneurs need capital for store improvement, increased workforce, increased production of goods, and others. Most B40 entrepreneurs are not eligible for a bank loan. They are too dependent on competitive sources such as TEKUN National, People's Trust Council (MARA), Perbadanan Usahawan Nasional Berhad (PUNB), and others. A strong business can be formed through training and learning. This study aims to determine the main reason for and issue related to low credit scores among B40 female entrepreneurs and to implement training strategies for these groups. This study involved 20 B40 female entrepreneurs in PPR Kerinchi, Kuala Lumpur. The findings have revealed that most informants have poor financial management, affecting their credit score and bankability. Thus, financial literacy programs are crucial to better understand entrepreneurship and finance in a more structured and systematic way. Dapur Mawar was held under the guidance of experienced speakers from public universities and the private sector to provide practical knowledge about financial management. Participants will be exposed to theoretical and practical knowledge for six months through five structured training modules.